2021
DOI: 10.1111/joca.12399
|View full text |Cite
|
Sign up to set email alerts
|

Covid‐19 pandemic and consumer‐employee‐organization wellbeing: A dynamic capability theory approach

Abstract: The consumers, employees, and organizations have been deeply impacted by Covid-19 pandemic. The present study offers a detailed coping mechanism for organizations based on the extant literature and content analysis of responses of senior management executives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 83 publications
0
105
0
1
Order By: Relevance
“…They further discussed paradoxes explaining the nexus between the consumption of technology and consumer vulnerability. Nayal et al (2021) identified various coping strategies for firms to take care of the employee and customer well-being. Digitalization and innovation emerged as the two focus areas for adoption by firms for their survival post-COVID-19.…”
Section: Backg Round Liter Aturementioning
confidence: 99%
“…They further discussed paradoxes explaining the nexus between the consumption of technology and consumer vulnerability. Nayal et al (2021) identified various coping strategies for firms to take care of the employee and customer well-being. Digitalization and innovation emerged as the two focus areas for adoption by firms for their survival post-COVID-19.…”
Section: Backg Round Liter Aturementioning
confidence: 99%
“…Service provision based on digital and artificial intelligence technology has become a possible solution to replace human service provision ( Nayal et al, 2021 ), triggering changes in consumer behavior by using technology-mediated services (such as robots) to replace manual services ( Kim et al, 2021 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Other papers examined consumers' financial positions with regards to the pandemic including financial preparedness and pandemic prevention behaviors (Warmath et al, 2022 ) as well as financial changes for parents before versus during the pandemic (Garrison et al, 2022 ). Lastly, other research took more of a macro focus outside of purely centering around the consumer looking at pandemic consumption behavior changes and governmental regulations (Güngördü Belbağ, 2022 ) and firms' response to changed pandemic‐related consumption habits (Nayal et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%